Plato’s Prescription - Thomas Sutherland (Media Theory)
In certain corners of media theory, the fanciful origin myth of writing furnished in Plato’s Phaedrus, one of his most enigmatic and intricate dialogues, has in turn come to serve as the origin myth for media critique itself. And yet, having been committed to writing, this is an origin myth that underwrites both its own non-originarity and non-truth, its very status as a written text ensuring it will never meet the criteria it sets for a reasoned account of things. This antinomy is not a shortcoming of the dialogue though, but a performative device, encouraging the reader to involve themselves in the dialogue and reflect upon their own relationship to it as audience. Plato does not proscribe writing, but he does prescribe a means for guiding one’s soul onto the path of knowledge – a prescription enacted within his writing itself, even as it points beyond the limits of the written word. The Phaedrus is not just diagnostic, but therapeutic.